2006
DOI: 10.1158/0008-5472.can-06-1968
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Role for AKT3 in the Genesis of Ovarian Cancer through Modulation of G2-M Phase Transition

Abstract: Ovarian cancer is the major cause of death from gynecological malignancy, and there is an urgent need for new therapeutic targets. The phosphatidylinositol 3-kinase (PI3K)/AKT pathway has been strongly implicated in the genesis of ovarian cancer. However, to identify and evaluate potential targets for therapeutic intervention, it is critical to understand the mechanism by which the PI3K/AKT pathway facilitates ovarian carcinogenesis. Here, we show that AKT3 is highly expressed in 19 of 92 primary ovarian tumor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 45 publications
6
77
2
Order By: Relevance
“…Dysregulation of putative target genes within these lists have been described in ovarian cancer. [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] E-cadherin and acatenin, components of the cadherin pathway, have previously been found to be dysregulated in metatstatic ovarian carcinoma and serous effusions. [79][80][81] Polymorphisms in cyclin D2 and protein kinase C isoform expression have been linked with prognosis in ovarian carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of putative target genes within these lists have been described in ovarian cancer. [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] E-cadherin and acatenin, components of the cadherin pathway, have previously been found to be dysregulated in metatstatic ovarian carcinoma and serous effusions. [79][80][81] Polymorphisms in cyclin D2 and protein kinase C isoform expression have been linked with prognosis in ovarian carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…87,88 AKT3, a component of the T-cell activation pathway, has been found to be highly expressed in a subset of ovarian serous carcinomas, and has been implicated as a key mediator of ovarian oncogenesis by the PI3K/AKT pathway. 78 PIK3R1, part of the same family of lipid kinases has also been implicated as an oncogene in ovarian tumourigenesis. 86 These putative targets indicate that miR-195 and miR-497 may have multiple biological roles in primary peritoneal carcinoma tumourigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…AKT mediates survival signals that protect cells from apoptosis and is a potentially important therapeutic target. AKT3 levels in various ovarian cancer cell lines correlate with total AKT activity and proliferation rates, suggesting an important role in the genesis of at least one subset of ovarian cancer (Cristiano et al, 2006). Altomare et al (2004) suggested that low AKT activity is associated with chemotherapy resistance in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cristiano et al (106) reported upregulation of Akt3 in 20% of ovarian tumors. Their data showed that ablation of Akt3 with shRNA resulted in decreased proliferation of ovarian tumor cells by arresting cell cycle progression at G2/M (106).…”
Section: Akt3 Deregulation In Other Types Of Cancermentioning
confidence: 99%